Research of Magnetic Field Influence on the Offset and Sensitivity of Magnetoresistive Sensor Readings - Markevicius, V.; Cepenas, M.; Navikas, D.; Valinevicius, A.; Andriukaitis, D. (Elektronika ir Elektrotechnika, 2013)
The article covers analysis of magnetic fieldsensor LSM303DLH with auxiliary components (R, C). A pairof Helmholtz coils were designed and examined. Experimentalequipment able to create magnetic field of magnitude up to1000G was produced. Research determined that residual offsetin measurement of magnetic field is observed at magnitudes ofexternal magnetic field reaching 20-50 G, depending onmagnetization of the sensor. Sensitivity of the sensor is notaffected by magnetization therefore offset can be eliminatedduring dynamic measurement of magnetic field. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3465